Acute and mixed alcohol intoxications in asylum seekers presenting to an urban emergency department in Switzerland - Adam D. Brown; Martin Müller; Trevor Hirschi; Jonathan F. Henssler; Katharina Rönz; Aristomenis K. Exadaktylos; David Srivastava (BMC, 2019)
Abstract Background Previous studies have reported an increase in alcohol-and-mixed intoxication (AAMI)-related emergency department (ED) admissions, but less is known about the incidence and characteristics of AAMI admissions to EDs among asylum-seeking patients. Asylum seeking patients may be at higher risk for AAMI due stressors associated with forced migration. The aim of this study was to determine the proportional incidence, population characteristics, and predictors of ED admissions due to AAMI among patients with a residency status of asylum seeker as compared to those with a residency status of Swiss-national. Methods This retrospective analysis included all medical consultations from a large, adult ED in Switzerland between January 1, 2013 to December 31, 2016. The residency status of consultations was established if possible, and AAMI was determined utilizing a two-step screening procedure, blinded for residency status. A multivariable logistic regression was performed to determine the odds of AAMI in asylum-seeking patient consultations compared to consultations for Swiss-national patients. In addition, patient characteristics among asylum seekers admitted for AAMI were compared to patients with Swiss-national residency status for AAMI. Results In total, 117,716 eligible consultations (Swiss-national patient consultations: n = 115,226 and asylum-seeker consultations: n = 2490) were included in this study. The proportional incidence of AAMI among asylum seekers was 3.7% (n = 92) compared to 1.6% (n = 1841) among the Swiss-national patients. AAMI in asylum seekers was associated with higher levels of trauma (37.0% vs. 23.5%, p = 0.003), and hospital admission (35.4% vs. 14.1%, p < 0.001), but a smaller proportion of chronic alcohol consumption (13.0% vs. 43.5%, p < 0.001), and psychiatric referrals (26.1% vs. 49.0%, p < 0.001). Multivariable analysis controlling for age, sex, triage category, weekend admission, year of admission, and multiple visits showed a 1.6 times higher odds (95% CI: 1.3, 2.0; p < 0.001) for an AAMI-related ED consultation in asylum seeking patients. Conclusions These findings show that individuals seeking asylum in a high-income country may be at greater risk for AAMI-related admission than the local population. Given the observed association between AAMI-related ED admissions and trauma, suicidality, and psychiatric referrals among this subpopulation, the data also suggests that co-morbid mental health disorders associated with forced displacement may contribute to hazardous alcohol use.